The syntax of question (WH-) word constructions in Venda : Mboswobeni Elvis Tshikhwalivha. - Tshikhwalivha, Mboswobeni Elvis (Stellenbosch : Stellenbosch University, 2012)
Study project (M.A.) -- University of Stellenbosch, 1995.